Satisfaction with oral anticoagulants in patients with atrial fibrillation - Suárez Fernández C; Castilla-Guerra L; Cantero Hinojosa J; Suriñach JM; Acosta de Bilbao F; Tamarit JJ; Diaz Diaz JL; Hernandez JL; Pose A; Montero-Pérez-Barquero M; Roquer J; Gállego J; et al. (Patient Preference and Adherence, 2018)
Carmen Suárez Fernández,1 Luis Castilla-Guerra,2 Jesus Cantero Hinojosa,3 Josep Maria Suriñach,4 Fernando Acosta de Bilbao,5 Juan José Tamarit,6 José Luis Diaz Diaz,7 Jose Luis Hernandez,8 Antonio Pose,9 Manuel Montero-Pérez-Barquero,10 Jaume Roquer,11 Jaime Gállego,12 José Vivancos,13 Jose María Mostaza141Internal Medicine Service, Hospital Universitario de La Princesa, Madrid, 2Internal Medicine Department, Hospital Virgen Macarena, Seville, 3Internal Medicine Service, Hospital San Cecilio, Granada, 4Internal Medicine Service, Hospital Vall D Hebron, Barcelona, 5Internal Medicine Service, Complejo Hospitalario Universitario Insular Materno-Infantil, Las Palmas de Gran Canaria, 6Internal Medicine Service, Hospital General De Valencia, Valencia, 7Internal Medicine Service, Complejo Universitario Hospitalario de A Coruña, La Coruña, 8Internal Medicine Service, Hospital Marqués de Valdecilla, Universidad de Cantabria, Santander, 9Internal Medicine Service, Complejo Hospitalario Universitario de Santiago de Compostela, Santiago de Compostela, 10Internal Medicine Service, Instituto Maimónides de Investigación Biomédica de Córdoba (IMIBIC), Hospital Reina Sofía, Universidad de Córdoba, Córdoba, 11Neurology Service, Hospital del Mar, Barcelona, 12Neurology Service, Complejo Hospitalario de Navarra, Pamplona, Navarra, 13Neurology Service, Hospital Universitario de La Princesa, Instituto de Investigación Sanitaria La Princesa, Madrid, 14Internal Medicine Service, Hospital Carlos III, Madrid, Spain Background: Although, by itself, atrial fibrillation is associated with an impairment of quality of life antithrombotic therapy may play a role.Objective: To evaluate the satisfaction with anticoagulant treatment in patients with nonvalvular atrial fibrillation who attended internal medicine departments in Spain.Methods: Patients from two different cross-sectional studies were combined. To measure the satisfaction with anticoagulant treatment, the Anti-Clot-Treatment Scale (ACTS) questionnaire was completed by every patient. A multivariate analysis was performed to determine the variables associated with satisfaction of patients receiving oral anticoagulants.Results: A total of 1,309 patients (mean age 78.5±8.4 years; 49.3% men; CHA2DS2VASC 4.9±1.5; HAS-BLED 2.0±0.9) were included in the study, of whom 902 (68.9%) were taking vitamin K antagonists (VKA) and 407 (31.1%) direct oral anticoagulants (DOACs). Overall, satisfaction with oral anticoagulation was high (ACTS Burdens scale 49.69±9.45; ACTS Benefits scale 11.35±2.61). The perceived burdens with anticoagulant treatment were lower in men, as well as in patients with no dependency, normal renal function, who were not polymedicated, or who had moderate bleeding risk. Among patients taking VKA, those subjects with a lower number of International Normalized Ratio (INR) determinations in the last 6 months or with an optimal time in the therapeutic range exhibited a lower perceived burden. Patients taking DOACs (vs VKA) showed a lower perceived burden with anticoagulation. Benefits with anticoagulation were higher in men, younger patients, those with no dependency, or low bleeding risk. Perceived benefits were higher in patients taking DOACs (vs VKA).Conclusion: Satisfaction with oral anticoagulation was high in patients with nonvalvular atrial fibrillation, who were attending internal medicine departments daily in Spain. Among patients taking VKA, those subjects with a lower number of INR determinations in the last 6 months or with an optimal time in the therapeutic range exhibited a lower perceived burden with anticoagulant therapy. Patients taking DOACs (vs VKA) showed lower perceived burdens and higher perceived benefits with anticoagulation. Keywords: atrial fibrillation, benefit, burdens, direct oral anticoagulants, satisfaction, vitamin K antagonists